A comprehensive review of hydrogels as potential drug carriers for anticancer therapies: Properties, development and future prospects - Renu Baweja; Rangnath Ravi; Ritvik Baweja; Sanjana Gupta; Ayush Sachan; Vavilala Pratyusha; Mohiuddin Khan Warsi; Shiv Dutt Purohit; Abhijeet Mishra; Razi Ahmad (Next Materials)
Hydrogels are porous hydrophilic polymers that can retain water and absorb water-based solutions. They have specific characteristics like permeability, elasticity, and stiffness, which can be used in various biomedical applications, especially cancer treatment. Due to high water content and flexibility similar to living tissues, hydrogels have wide-ranging biomedical uses. Crosslinking within hydrogels provides structural stability while enabling the absorption and release of water, solutes, and even drugs or biomolecules. Hydrogels with nanotechnology have synergistically led to the development of new environmentally friendly, biocompatible, and biodegradable targeted drug delivery systems. Among them, carbohydrate-based hydrogels with excellent biocompatibility are the best candidates for cancer treatment. Recently, hydrogels have emerged as promising drug carriers for cancer treatment. They minimize the severity of side effects compared to systemic chemotherapy and facilitate sustained drug delivery locally at specific tumor sites. The vast diversity in size, nature of the polymer used (natural or synthetic), and drug delivery route of various hydrogels used in cancer treatment are of great significance, which has been highlighted explicitly in this review. As research continues to refine hydrogel-based drug delivery systems, they offer hope for more effective and personalized treatment options, ultimately improving cancer patients' outcomes and quality of life.